Outer Retinal Tubulation in Advanced Age-Related Macular Degeneration: Optical Coherence Tomographic Findings Correspond to Histology - Schaal, Karen B. (Retina, 2015)
PURPOSE: To compare optical coherence tomography (OCT) and histology of outer retinal tubulation (ORT) secondary to advanced age-related macular degeneration (AMD) in patients and in post-mortem specimens, with particular attention to the basis of the hyper-reflective border of ORT. METHOD: A private referral practice (imaging) and an academic research laboratory (histology) collaborated on two retrospective case series. High-resolution OCT raster scans of 43 eyes (34 patients) manifesting ORT secondary to advanced AMD were compared to high-resolution histological sections through the fovea and superior perifovea of donor eyes (13 atrophic AMD and 40 neovascular AMD) preserved ≤4 hours after death. RESULTS: ORT seen on OCT corresponded to histologic findings of tubular structures comprised largely of cones lacking outer segments (OS) and lacking inner segments (IS). Four phases of cone degeneration were histologically distinguishable in ORT lumenal walls, nascent, mature, degenerate, and end-stage (IS and OS; IS only; no IS; no photoreceptors and only Müller cells forming external limiting membrane, ELM, respectively). Mitochondria, which are normally long and bundled within IS ellipsoids, were small and scattered within shrunken IS and cell bodies of surviving cones. A lumenal border was delimited by an ELM. ORT observed in closed and open configurations were distinguishable from cysts and photoreceptor islands on both OCT and histology. Hyper-reflective lumenal material seen on OCT represents trapped retinal pigment epithelium (RPE) and non-RPE cells. CONCLUSIONS: The defining OCT features of ORT are location in the outer nuclear layer (ONL), a hyper-reflective band differentiating it from cysts, and RPE that is either dysmorphic or absent. ORT histologic and OCT findings corresponded in regard to composition, location, shape, and stages of formation. The reflectivity of ORT lumenal walls on OCT apparently does not require an OS or an IS/OS junction, indicating an independent reflectivity source, possibly mitochondria, in the IS.